Hubungan Stres dan Merokok dengan Kejadian Hipertensi di Kelurahan Sei Langkai Wilayah Kerja UPTD Puskesmas Sei Langkai Kota Batam Tahun 2024 - Suryani Suryani; Afif D. Alba; Nelli Roza (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Hypertension is a "silent disease" with a high prevalence that can be triggered by modifiable risk factors such as stress and smoking. Sei Langkai Community Health Center shows the highest hypertension service rate (20.12%) in Batam City with Sei Langkai Village having 50% of hypertension sufferers from the health center's working area. The purpose of this study was to analyze the relationship between stress and smoking with the incidence of hypertension in Sei Langkai Village, the Working Area of ​​UPTD Sei Langkai Community Health Center, Batam City. This research method is an analytical observational study with a cross-sectional design. The accessible population is residents aged >17 years in RW 17 RT 05 Sei Langkai Village (334 people). A sample of 75 respondents was selected using a cluster random sampling technique. Data collection used the Perceived Stress Scale (PSS) questionnaire to measure stress and the Fagerstrom Test for Nicotine Dependence (FTND) to measure smoking dependence, as well as blood pressure observations. Data analysis used the chi-square test and Spearman correlation. The results showed a significant association between stress and hypertension (p=0.001; PR=5.688; 95% CI: 2.200-14.705). Of the 47 respondents experiencing stress, 87.2% had hypertension. There was a significant association between smoking and hypertension (p<0.001; r=0.585). Of the 28 respondents with heavy smoking habits, 96.4% had hypertension. The study concluded that stress and smoking are significantly associated with hypertension. Respondents with stress had a 5.688-fold higher risk of developing hypertension. The more severe the smoking habits, the higher the risk of hypertension.